Amphibole genesis via metasomatic reaction with clinopyroxene in mantle xenoliths from Victoria Land, Antarctica - COLTORTI, Massimo; BECCALUVA, Luigi; BONADIMAN, Costanza; FACCINI, Barbara; SIENA, Franca; NTAFLOS T (Lithos, 2004)
Petrographic and major and trace element geochemical features of clinopyroxene, amphibole and glass from composite xenoliths from Mt. Melbourne and Mt. Overlord (Victoria Land, Antarctica) were investigated. Amphibole disseminated in the peridotite matrix appears to grow around clinopyroxene and spinel, and is often associated with high-TiO2 silicate glass. Clinopyroxene presents a wide range of compositions, from primary unmetasomatized diopside to high-MgO salite, with REE patterns varying from flat (at Yb-N 5Xchondrite) to slightly enriched [(La/Yb)(N) 2.7-4.2] at higher HREE contents (Yb-N 9.3-14.3). Amphibole also occurs in veins which, in few cases, grade into glass-rich veins before vanishing into the peridotite. Glasses are not related to amphibole destabilization; on the contrary, they appear to be strictly related to its formation. No chemical differences were noted between glasses related to disseminated or vein amphiboles. Their geochemical features favour a Na-alkaline silicate melt as the metasomatizing agent. Mass balance calculations were used to model the reactions producing amphibole from primary clinopyroxene, and to highlight the nature of the metasomatic agent/s. Trace element contents of the inferred melt/s are comparable to those of the most undersaturated magma found in the area, suggesting a strong link between metasomatism and the magmatism of the Ross Sea Rift system. This hypothesis is further strengthened by the analogy between trace element patterns of clinopyroxene associated with amphibole (cpx-A) and those of clinopyroxene contaminated by the host basalt (cpxBas). On the basis of the Mg/Fe diffusion model, the difference in mg# between these two clinopyroxenes was used to estimate the timing of the basalt infiltration and amphibole formation. Finally, various models for disseminated and vein amphibole relationships are recalled and their application to Antarctic amphiboles is tested. The petrographic and geochemical features of disseminated amphiboles, in fact, do not support the ...